2018
DOI: 10.1002/qre.2377
|View full text |Cite
|
Sign up to set email alerts
|

Hotelling's T2 control charts with fixed and variable sample sizes for monitoring short production runs

Abstract: Short production runs are common in enterprises that require a high degree of flexibility and variety in manufacturing processes. To date, past research on short production runs has little focus on the multivariate control charts. In view of this, fixed sample size (FSS) and variable sample size (VSS) Hotelling's T2 charts are designed to monitor the process mean when the production horizon is finite. Optimal parameters to minimize the out‐of‐control (1) truncated average run length (TARL) and (2) expected TAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Let { Y 1 , Y 2 , …, Y n ( i ) } be a normally distributed multivariate random variable with sample size n ( i ) from the p ‐variate mean vector, μ 0 and covariance matrix, ∑ 0 . Then, the statistic of Hotelling's T 2 is obtained as 22 Ti2=nfalse(ifalse)(bold-italicYtrue‾iμ0)T01false(trueYibold-italicμ0false)wherei=1,2,,I. …”
Section: Shewhart Hotelling's T2 Chart For a Finite Horizon Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Let { Y 1 , Y 2 , …, Y n ( i ) } be a normally distributed multivariate random variable with sample size n ( i ) from the p ‐variate mean vector, μ 0 and covariance matrix, ∑ 0 . Then, the statistic of Hotelling's T 2 is obtained as 22 Ti2=nfalse(ifalse)(bold-italicYtrue‾iμ0)T01false(trueYibold-italicμ0false)wherei=1,2,,I. …”
Section: Shewhart Hotelling's T2 Chart For a Finite Horizon Processmentioning
confidence: 99%
“…Celano et al 20 and Khatun et al 21 then developed the joint Shewhart charts and one‐sided Shewhart multivariate coefficient of variation charts in a finite horizon process, respectively. More recently, Chong et al 22 developed the SH and variable sample size (VSS) Hotelling's T 2 charts to monitor the short production runs.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the choice of the monitoring scheme does not heavily depend on the distribution of the quality characteristic. Chong et al [47] proposed the multivariate fixed sample size and VSS Hotelling's T 2 short-run charts to monitor the mean shift in short production runs. Based on the comparison between the control charts, the VSS Hotelling's T 2 short-run chart surpasses its fixed sample size counterpart for most shift sizes.…”
Section: Introductionmentioning
confidence: 99%
“…19 Shepherd et al 20 proposed a Hotelling T 2 control chart based on shrunken covariance estimator. Many researchers have studied the aspects of Hotelling T 2 control chart including Chew et al, 21 Chong et al, 22 Dargopatil and Ghute, 23 and Sabahno et al 24 These estimators have some weaknesses. One is their high sensitivity to the presence of outliers, which leads to malfunction of the Hotelling T 2 control chart.…”
Section: Introductionmentioning
confidence: 99%